PENGARUH FAKTOR STRES DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KARYAWAN DI BANK BNI KC MAMUJU, (Persero) Tbk - ADINUGROHO, IWAN (LPPM Universitas Muhammadiyah Mamuju, 2019)
Stress itself can be interpreted as a condition of tension that affects emotions, thought processes and physical condition of a person. motivation can be interpreted as internal and external impulses in a person as indicated by the existence; passion and interest; encouragement and needs; hopes and ideals; appreciation and respect. This study aims to determine the effect of work stress and work motivation on employee work productivity at PT. Bank BNI KC Mamuju (Persero) Tbk. The population in this study were 114 people. In the sample withdrawal by means of the Disproportionate Stratified Random Sampling obtained a sample of 53 people. Data analysis techniques used are qualitative and quantitative approaches. Based on the calculation of Pearson product moment correlation coefficient obtained 0.788, meaning that the relationship of work stress factors to work productivity is classified as a relationship / strong correlation. The coefficient of determination obtained 62.1%, this shows that work productivity can be influenced by stress factors of 62.1%. While the coefficient of determination obtained 50.4%, this shows that work productivity can be influenced by motivational factors of 50.4%. From the hypothesis test in the research, the tcount value is greater than the t table value (9,162> 2,007), it means an alternative hypothesis ( Ha) accepted, the results of simple linear regression calculations obtained by the equation Y = 13.41 + 0.76X means that which shows a positive direction. Based on the calculated F test results obtained 83,622 while the F table of 4,03 from these results known F count> F table, and the significance of 0,000 or ≤ α = 0.05 so it can be concluded that Ho is rejected and Ha is accepted. To reduce work stress on activities at PT Bank BNI KC Mamuju (Persero) Tbk by increasing harmonious relationships between superiors and employees establishing cooperation and mutually giving good motivation between colleagues and giving tasks in accordance with employee capabilities.